ECONOMIC ADAPTATION STRATEGY FOR PEDICAB RIDERS FACING MODERN COMPETITION IN THE CITY OF SOLO - Woro Wijayanti; Vincentius Hadi Wiyono; Rr. Retno Sugiharti (Journal of Applied Economics in Developing Countries, 2022)
Modernization has impacted all aspects of life, including transportation. As technology advances, innovations in transportation increase, leading to more convenient options like motorbike taxis, traditional taxis, and online-based transportation. This progress negatively affects conventional vehicles, such as pedicabs. This research focuses on modernization's impact on pedicab drivers in Solo, examining their characteristics and economic adaptation strategies. Data were collected through questionnaires, interviews, and observations. The analysis revealed that age, education level, and address significantly influence drivers' decisions to take side jobs, while the number of dependents and monthly income do not. Pedicab drivers adapt economically by having part-time jobs, saving money, and receiving support from working family members.